Program dan Biaya Reklamasi Untuk Jaminan Reklamasi Berdasarkan KEPMEN ESDM No. 1827 Tahun 2018 di PT. TRI ABADI MINERAL (TAM) - Supardi (JURUTERA - Jurnal Umum Teknik Terapan, 2021)
Indonesia is a country that has natural resources (SDA). Mining materials are non-renewable natural resources. Mining materials include stone sand, silver, gold, copper, natural gas, and oil. Manokwari Regency is an area that has abundant natural resources. The company's mining activities have provided a reasonably comprehensive source of income for the regions in the last few decades. Mining has also triggered environmental problems that are closely related to land degradation. To overcome environmental problems from mining activities, it is necessary to the reclamation of ex-mining land. This paper aims to obtain a reclamation program, determine the form of revegetation, and obtain a direct and indirect cost budget at PT TAM. The mining area is carried out with an area of 9.1 Ha consisting of an area around the mine along ± 1.86 Km and supporting facilities with an area of 2.05 Ha such as workshops, offices, housing, and a stone crusher. Moreover, the rest is the mining area. The Reclamation activity program is carried out at mine sites, mining roads, and supporting facilities, with the reclamation technique carried out starting from the arrangement of the land surface, making drainage, sedimented pond, and revegetation. Revegetation is carried out in 3 stages. Among others, the first stage is planting cover crops. The second stage is planting the main crop and maintenance. The amount of reclamation guarantee must be paid by PT. Tri Abadi Mineral (TAM) is Rp. 101.260.125,-.